The influence of financial knowledge, financial socialization, financial behaviour and financial strain on young adults' financial well-being - Sabri, Mohamad Fazli; Anthony, Mervin; Wijekoon, Rusitha; Ahmad Suhaimi, Siti Shazwani; Abdul Rahim, Husniyah; Magli, Amira Shazana; Mat Isa, Muhammad Pisol (Human Resource Management Academic Research Society, 2021)
Financial well-being refers to one’s overall satisfaction with their current financial condition, and it plays a significant part in young adults’ overall success as well as their ability to overcome psychological health concerns. It has become a crucial concern for individuals, households, societies, and countries in recent years, yet research on the subject is sparse and dispersed among fields. As a result, the current research assessed an empirical financial wellbeing model based on Malaysian young adults’ financial knowledge, financial socialization, financial behavior and financial strain. A multi stage random sampling method was performed to draw a representative sample of Malaysian young adults, and 651 duly filled responses were received through the self-administered questionnaire. As stated by the multiple regression results, 16.1% of the total variance of financial well-being was clarified by the model. All four financial well-being determinants examined (financial knowledge, financial socialization, financial behavior, financial strain) were revealed significant, and only financial strain had a negative relationship with financial well-being. Therefore, current study has both the theoretical and practical contributions, and offers experts with actionable insights regarding the determinants of young adults’ financial well-being when designing policies to uplift their financial well-being over time.